How blind people relate to the visual arts?: a case study on artistic references, accessibility and aesthetic fruition (Revista de Ensino em Artes, Moda e Design, 2023)
This article presents the results obtained in a research on the reception of visually impaired people to the visual arts, investigating the repertoire of known works, the current state of accessibility, as well as reports of aesthetic experiences. This case study, a quali-quantitative research, was carried out through a survey with people with visual impairments, most of them attendees of the Benjamin Constant Institute, a century-old institution located in the city of Rio de Janeiro. The results revealed artistic references mostly of European origin, with the aggravating factor that their forms are unknown, that is, there was no intermediation through audio description (AD) and/or tactile material. Regarding accessibility in museums and cultural institutions, the results point to the lack of opportunities and carelessness with this audience. In the case of so-called inclusive events, the inefficiency of audio description as a unique accessibility resource for the visual arts was observed, emphasizing the importance of touching tactile materials with their respective audio description. The tactile perception of sculptures proved to be a powerful catalyst for aesthetic fruition, justifying the defense of the possibility of touching originals of three-dimensional works for people with visual impairments.
Keywords: visual impairment; visual arts; accessibility